Faktor Pengaruh Mahasiswa dalam Berwirausaha di Surakarta - Atik Lusia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Currently, there are many unemployed people who are college graduates. This is due to the limited abilities possessed by graduates and the needs desired by industry. At the tertiary level, it is necessary to direct and educate students to have an entrepreneurial character so that they can develop in the outside world. This research focuses on finding out students' interest in creating or running a business. The sample used as data is students in Surakarta who have completed entrepreneurship courses. The type of research used is quantitative, with techniques used including instrument testing, multiple regression analysis, partial hypothesis testing, and coefficient of determination. Research respondents were obtained through a questionnaire with a Likert scale and using SPSS. The results of this research state that all variables have a significant effect on students' interest in entrepreneurship. Based on the research results, universities need to improve Entrepreneurship Education and Motivation because it can be the basis or motivation that comes from within students to set up a business. Apart from that, it is also necessary to improve those that come from outside such as the Environment and Income Expectations